Corporate Entrepreneurship, Disruptive Business Model Innovation Adoption, and Its Performance: The Case of the Newspaper Industry. Issue 3 (June 2016) - Karimi, Jahangir; Walter, Zhiping
Abstract : Recently, Internet and digitization, along with major news and information companies, have disrupted traditional newspaper companies' business models, and raised serious concerns about the future viability of the print newspaper industry. This study provides a theoretical viewpoint, supported by empirical evidence from the newspaper industry, on how prominent corporate entrepreneurship attributes impact disruptive business model innovation adoption, and how such adoption impacts business model performance. It finds that, while autonomy, risk-taking, and proactiveness do have positive associations with the extent of adoption of disruptive business model innovation, innovativeness does not. Further, disruptive business model innovation adoption has a nonlinear association with business model performance. We conclude the paper by discussing theoretical implications of the study and by providing strategies that entrepreneurs and technology managers can use to adjust their corporate entrepreneurship activities in their effort to successfully adopt disruptive business model innovation.